2022
DOI: 10.3390/molecules27030846
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Study of Hypoglycemic Constituents from Myrica rubra Pomace

Abstract: Myrica rubra pomace accounts for 20% of the fruit’s weight that is not utilized when it is juiced. The pomace contains bioactive phenolic substances such as anthocyanins and flavonoids. To improve the utilization value of Myrica rubra pomace, an optimized extraction method for the residual polyphenols was developed using response surface methodology (RSM). The resulting extract was analyzed by high performance liquid chromatography (HPLC), and the in vitro hypoglycemic activity and antioxidant activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Moreover, myricetrin and myricetin showed excellent ROS scavenging ability. Similarly, Chang et al found that myricitrin, cyanidin-O-glucoside, hyperoside, and quercitrin in the pomace of Myrica rubra have good antioxidant and α-glucosidase inhibition abilities, and myricitrin showed the highest α-glucosidase inhibitory activity among the four compounds [27]. The phenolics of Myrica rubra exert anti-glycative actions by scavenging free radicals, trapping reactive α-dicarbonyls, inactivating transition metals, and interacting with glycation-related proteins [28].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, myricetrin and myricetin showed excellent ROS scavenging ability. Similarly, Chang et al found that myricitrin, cyanidin-O-glucoside, hyperoside, and quercitrin in the pomace of Myrica rubra have good antioxidant and α-glucosidase inhibition abilities, and myricitrin showed the highest α-glucosidase inhibitory activity among the four compounds [27]. The phenolics of Myrica rubra exert anti-glycative actions by scavenging free radicals, trapping reactive α-dicarbonyls, inactivating transition metals, and interacting with glycation-related proteins [28].…”
Section: Discussionmentioning
confidence: 96%